The Effectiveness of Chocolate in Reducing the Number of Methicillin-Resistant Staphylococcus aureus Colonies in Rattus norvegicus - Edy Suwandi; Ari Nuswantoro; Sugito Sugito; Desi Wahyumarniasari; Muhammad Reza Setiawan; Dinasti Aprillia; Devi Nurfitri Bintang (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Chocolate has long been understood to provide positive emotions and a good mood if consumed in moderation. Chocolate contains prebiotics naturally from its constituent ingredients produced during the production process. Prebiotics, frequently oligosaccharides, are substances which cannot be metabolized by the human digestive system but can be employed by a group of bacteria in the gut, understood as probiotics. The positive relationship among them provides benefits for the host in eliminating pathogens. One of the well-known pathogens which frequently cause infection either in the community or in hospitals is methicillin-resistant Staphylococcus aureus (MRSA). Since it was first identified in 1960, MRSA has caused health problems until today. Research conducted on two groups of Rattus norvegicus infected with MRSA and then fed chocolate revealed a decrease in the average number of bacterial colonies on the skin compared to the control group. In the group fed chocolate at a dose of 50 mg/day, the bacterial colonies decreased to 1.28 x 108 CFU/cm2 in 7 days, lower than in the control group (1.46 x 108 CFU/cm2) at the same time. While those fed 75 mg/day chocolate decreased to 2.70 x 107 CFU/cm2 and the three groups were significantly different (0.000<0.05). Prebiotics fermented by probiotics release short-chain fatty acids (SCFA), which compete with the pathogens for attaching to the epithelial wall so that pathogens lose space and nutrients to survive. However, the adverse effect of chocolate may occur because it contains sugar which is a nutrient for bacteria, but if the balance of normal flora and adequate intake of prebiotics are administered, the pathogen could be eliminated.